Growth, sporulation and toxin production by Bacillus thuringiensis isolates in media based on mustard-seed meal (Bangladesh Journal of Microbiology, 2011)
This study was aimed at the large scale production and application of Bacillus thuringiensis (Bt) biopesticide in Bangladesh agriculture from locally available cheap raw materials. B. thuringiensis subsp. kurstaki HD-73 (reference strain) and two other indigenous isolates of B. thuringiensis namely Bt-Soil-47 and Bt-Insect-1i demonstrated satisfactory growth of sporulation and endotoxin production in a medium prepared from de-fatted mustard-seed meal (oil cake) as carbon and nitrogen sources at 30°C. A correlation of growth, sporulation and endotoxin production pattern was obtained through the systematic study over the period of 72 h. Time course study of the growth of all three Bt isolates demonstrated similar pattern; however, spore-crystal complex formation of the indigenous Bt isolates was different with respect to the reference strain. The two indigenous isolates formed the maximum sporecrystal complex at 36 h, whereas the reference strain did the same at 66 h. Hence, the productivity of endotoxin formation of the indigenous isolates, 34.30×10-3 and 37.50times;10-3 g/L/h respectively, were higher than that of the reference strain (21.37×10-3 g/L/h). Spore-crystal complex of the bacilli was recovered as dry powder which can be applied suitably in field to test their insecticidal activity. Molecular size of endotoxin of the isolates analyzed by SDS-PAGE resembled the typical sizes of the δ-endotoxin of Bacillus thuringiensis. Keywords: Bacillus thuringiensis; spore-crystal complex; δ-endotoxin. DOI: http://dx.doi.org/10.3329/bjm.v27i2.9172 BJM 2010; 27(2): 51-55